From seismic hazards to resilient cities: the contribution of engineering geology - Martino, Salvatore; Varone, Chiara (Italian journal of engineering geology and environment, 2020)
<span data-sheets-value="{"1":2,"2":"Different types of natural hazard affect the surface of the Earth, exposing human communities to high-risk conditions. This fact makes it imperative to identify strategies for preventing, responding to, managing, and recovering from natural disasters. It is within this framework that the concept of “resilience” has arisen. Achieving a resilient condition is the only way to mitigate the impact of and the losses due to natural disasters, as well as to protect the health and well-being of communities. The paper discusses the contribution that engineering geology can provide to increasing the structural and social resilience of communities to the impact of earthquakes. Creating awareness of engineering geology applications in society and among public institutions can enhance social resilience, while promoting the understanding of natural processes and their interactions with man-made structures and the environment can improve the structural component of resilience. The paper describes the role of engineering geology as a new player in strengthening community resilience, suggesting the need for a multidisciplinary approach to achieving a resilient condition."}" data-sheets-userformat="{"2":15235,"3":{"1":0},"4":{"1":3,"3":2},"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">Different types of natural hazard affect the surface of the Earth, exposing human communities to high-risk conditions. This fact makes it imperative to identify strategies for preventing, responding to, managing, and recovering from natural disasters. It is within this framework that the concept of “resilience” has arisen. Achieving a resilient condition is the only way to mitigate the impact of and the losses due to natural disasters, as well as to protect the health and well-being of communities. The paper discusses the contribution that engineering geology can provide to increasing the structural and social resilience of communities to the impact of earthquakes. Creating awareness of engineering geology applications in society and among public institutions can enhance social resilience, while promoting the understanding of natural processes and their interactions with man-made structures and the environment can improve the structural component of resilience. The paper describes the role of engineering geology as a new player in strengthening community resilience, suggesting the need for a multidisciplinary approach to achieving a resilient condition.